Balling gun‐induced trauma in cattle: clinical presentation, diagnosis and prevention. (29th June 2013) - Mann, S.; Nuss, K. A.; Feist, M.; Weber, B. K.; Zoller, D. K.; Metzner, M.
Abstract : Pharyngeal trauma in cattle can occur during the administration of oral medication using a balling gun. The number of cases of severe complications due to bolus application that have been referred to our hospital has increased from nil between 1996 and 2008 to three or four per year. In our experience, reports by bovine veterinarians of patients with severe and often fatal pharyngeal trauma, which were not referred to the clinic, have become more common in recent years as well. The incidence of this complication is likely to be higher than this number of referrals suggests. Diagnosis without the help of imaging techniques, such as radiography and endoscopy, may be difficult, especially in cases where exploration of the pharynx cannot be carried out, or is unable to confirm the absence or presence of a lesion. Prognosis is often poor in cases where perforation has been confirmed. Boluses are increasingly administered by the owners or farm personnel without the supervision of a veterinarian. In order to prevent losses due to balling gun‐induced injuries, the veterinarian plays a crucial role in giving advice to his clients. Five cases of cattle suffering from varying degrees of balling gun‐induced trauma are presented, and consideration is given to incorrect application techniques.